Case report: Synchronous prostate cancer and renal cell carcinoma with prostate cancer-origin metastases to adrenal and renal hilar lymph nodes - Zhang, Yaowen; Chen, Junru; Xu, Lijing; Hu, Xu; Zeng, Hao; Liu, Zhenhua (Frontiers in Oncology, 2024)
BackgroundSynchronous occurrence of prostate cancer (PCa) and renal cell carcinoma (RCC) is uncommon. RCC has a higher tendency to metastasize to the adrenal glands, renal hilar, and retroperitoneal lymph nodes compared to PCa. To date, there are no documented cases existing where metastatic tumors in these regions, observed in patients concurrently with PCa and RCC, have originated from the PCa rather than the RCC.Case presentationIn this case report, we described a 67-year-old male presented with dysuria for two months and left lower extremity edema for three days. Percutaneous biopsies revealed synchronous primary RCC and PCa. However, the origin of the metastatic tumors, especially those involving the adrenal glands, renal hilum, and retroperitoneal regions, remained undetermined. Subsequent surgical procedures identified that the metastatic lesions originated from the PCa, while the RCC was localized. Ultimately, the patient with metastatic hormone-sensitive prostate cancer (mHSPC) received combination therapy with rezvilutamide and goserelin, which resulted in a satisfactory treatment response.ConclusionIn patients with concurrent PCa and RCC, metastatic lesions in the adrenal glands, renal hilar, and retroperitoneal lymph nodes may also originate from the PCa. Accurate identification of the primary tumor and proper staging are critical for the appropriate management of patients with multiple primary malignancies with concurrent metastases.